Genomic selection in Canadian spruces - El-Kassaby, Yousry A.; Ratcliffe, Blaise; El-Dien, Omnia Gamal; Shuzhen, Sun; Chen, Charles; Cappa, Eduardo Pablo; Porth, Ilga M. (Springer, 2021)
The genetic gain of spruce (Picea spp.) breeding programs is impeded by long recurrent selection cycles stemming from biological constraints such as late expression of traits, weak juvenile mature correlations, and late onset of sexual maturity. Genomic selection (GS) is capable of addressing these barriers to improving the rate of genetic gain via early prediction of phenotypes using dense genetic marker arrays. Results from GS studies focused on spruce species in Canada thus far have produced encouraging results to capture additional genetic gain for wood quality.